Analisis Faktor Budaya Organisasi, Pengembangan Karir, dan Motivasi dalam Meningkatkan Kepuasan Kerja Karyawan - Hilda Pradina Faradiba; Aditya Syaiful Dhuhri (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to analyze how the factors of organizational culture, career development, and work motivation contribute to employee job satisfaction. Job satisfaction is a crucial component that affects employee productivity, retention, and performance in an organization. In today's competitive context, organizations must understand the factors that can increase job satisfaction to retain talented and committed employees. This study used a quantitative approach with a survey design, where data was collected through questionnaires distributed to 200 employees in various industrial sectors. The results of the analysis show that a positive organizational culture, clear career development programs, and high work motivation significantly affect the level of employee job satisfaction. A supportive organizational culture, with good communication and an inclusive work environment, increases employees' sense of satisfaction. In addition, opportunities for career development through training and promotion also contribute to job satisfaction. High work motivation, both intrinsic and extrinsic, was shown to have a strong relationship with job satisfaction. These findings emphasize the importance of integration between organizational culture, career development strategies, and work motivation in creating a satisfying and productive work environment.